KEDUDUKAN DEWAN PERWAKILAN RAKYAT DALAM PENETAPAN DAN PENGAWASAN APBN DI INDONESIA - Julfikar, Julfikar (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
The one of House of Representatives’ role (DPR) is overseeing. DPR is as the one of determinant of Indonesia government. DPR has crucial role and function for Indonesia citizen lives in all aspects. In constitution aspect, DPR has role to determine budget together with government. Budgeting function needs to be supervised if it’s not, the Indonesia development program will not be on target. DPR should give the guidance in budgeting process, because it is related of State Budget.